Katekismus Heidelberg: Sebuah Eksposisi Atas Pertanyaan Pertama khususnya kata “Penghiburan” - Timotius, Timotius; Putrawan, Bobby Kurnia (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2023)
The Heidelberg Catechism’s opening question, with its emphasis on “consolation,” represents a profound theological and pastoral exploration of the human condition. It underscores the enduring quest for true comfort, rooted in faith in Jesus Christ, and offers solace and hope amid life’s uncertainties and the inevitability of death. Understanding the historical context, theological depth, and practical implications of this question enhances one’s appreciation for the enduring relevance of the Heidelberg Catechism in the Christian tradition. Further study and reflection on its teachings can enrich the spiritual journey of believers seeking lasting consolation in their faith. This article aims to explain that the first question in the Helderberg Catechism is Theocentric. This is because there are scholars who say that the Heidelberg Catechism is very people-centered because it starts with a question that seems to tend to emphasize human needs. The author uses the literature method in this study. The final result of this study the author will show that the Helderberg Catechism is Theocentric, not People-Centered because the first question in the Helderberg Catechism is based on the awareness that God is the true source of comfort so that Christians only want to seek true comfort from God. Pertanyaan pembuka Katekismus Heidelberg, dengan penekanannya pada